1996
DOI: 10.1007/bf00418540
|View full text |Cite
|
Sign up to set email alerts
|

C-peptide improves autonomic nerve function in IDDM patients

Abstract: In order to determine the possible influence of C-peptide on nerve function, 12 insulin-dependent diabetic (IDDM) patients with symptoms of diabetic polyneuropathy were studied twice under euglycaemic conditions. Tests of autonomic nerve function (respiratory heart rate variability, acceleration and brake index during tilting), quantitative sensory threshold determinations, nerve conduction studies and clinical neurological examination were carried out before and during a 3-h i.v. infusion of either C-peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
58
2
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(63 citation statements)
references
References 35 publications
2
58
2
1
Order By: Relevance
“…Renewed interest in C-peptide was prompted by the finding that C-peptide may prevent or retard the development of microvascular complications in insulin-dependent diabetes mellitus (IDDM) patients [1]. Thus, C-peptide has been found to improve renal function [2,3], stimulate glucose transport in skeletal muscle [4,5], increase skeletal muscle blood flow and oxygen uptake [4,6], and improve autonomic and motor nerve function [7,8] in IDDM patients and in animals with experimental diabetes. The mechanism(s) behind these physiological effects are not fully known.…”
Section: Introductionmentioning
confidence: 99%
“…Renewed interest in C-peptide was prompted by the finding that C-peptide may prevent or retard the development of microvascular complications in insulin-dependent diabetes mellitus (IDDM) patients [1]. Thus, C-peptide has been found to improve renal function [2,3], stimulate glucose transport in skeletal muscle [4,5], increase skeletal muscle blood flow and oxygen uptake [4,6], and improve autonomic and motor nerve function [7,8] in IDDM patients and in animals with experimental diabetes. The mechanism(s) behind these physiological effects are not fully known.…”
Section: Introductionmentioning
confidence: 99%
“…Short time studies have reported beneficial effects of C-peptide on renal, sensory and autonomic abnormalities in Type I diabetic patients [19,20].…”
mentioning
confidence: 99%
“…In contrast, patients with type 2 diabetes, characterized by insulin resistance, often have normal or elevated C-peptide concentrations [7]. There is evidence that C-peptide may improve autonomic function in type 1 diabetes [14,15,23,27]. Our aim was to evaluate the acute effects of C-peptide on gastric emptying in patients with longstanding type 1 diabetes.…”
Section: Introductionmentioning
confidence: 92%